2000
DOI: 10.1128/iai.68.6.3485-3490.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hyphal Formation in Interactions of Candida albicans with Endothelial Cells

Abstract: The ability to change from yeast to hyphal morphology is a major virulence determinant of Candida albicans. Mutants with defined defects in filamentation regulatory pathways have reduced virulence in mice. However, is it poorly understood why hyphal formation is critical for C. albicans to cause hematogenously disseminated infections. We used recently constructed mutants to examine the role of hyphal formation in the interactions of C. albicans with endothelial cells in vitro. These interactions included the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(204 citation statements)
references
References 31 publications
8
192
0
4
Order By: Relevance
“…Differences in the virulence of cph1, efg1 single and the cph1/efg1 double mutants were found in a mouse model for systemic infection (Lo et al, 1997;Staib et al, 2002;Felk et al, 2002) and during interaction with mouse macrophages (Lo et al, 1997). Investigations using human tissues were performed with endothelial (Phan et al, 2000), intestinal and epidermal cells (Dieterich et al, 2002). Results from these experiments demonstrated a significantly decreased virulence phenotype only in the mutants lacking functional EFG1 but not for the cph1 single mutant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the virulence of cph1, efg1 single and the cph1/efg1 double mutants were found in a mouse model for systemic infection (Lo et al, 1997;Staib et al, 2002;Felk et al, 2002) and during interaction with mouse macrophages (Lo et al, 1997). Investigations using human tissues were performed with endothelial (Phan et al, 2000), intestinal and epidermal cells (Dieterich et al, 2002). Results from these experiments demonstrated a significantly decreased virulence phenotype only in the mutants lacking functional EFG1 but not for the cph1 single mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Efg1 (Stoldt et al, 1997;Bockmuhl & Ernst, 2001) and Cph1 (Bockmuhl & Ernst, 2001) have been identified as key transcriptional regulators for the cAMP-protein kinase (PKA) and the mitogen-activated protein kinase (MAPK) pathway, respectively. The role of these factors in morphogenesis and their relevance for Candida infections was studied using strains which lacked either functional Efg1, Cph1 or both factors (Brown & Gow, 1999;Stoldt et al, 1997;Bockmuhl & Ernst, 2001;Dieterich et al, 2002;Kohler & Fink, 1996;Leberer et al, 1997;Lo et al, 1997;Sonneborn et al, 1999b;Weide & Ernst, 1999;Lewis et al, 2002;Phan et al, 2000). The results obtained with these mutants suggested that disruption of CPH1 caused attenuated hyphal formation abilities on solid media while mutants lacking EFG1 failed to produce hyphal cells under most conditions investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate High [36,39,40] Damage None High [40,86] Dissemination Within the bloodstream Across epithelial barriers; interepithelial [18,22,36,46] Iron acquisition via ferritin…”
Section: Low Nonementioning
confidence: 99%
“…However, Efg1 also regulates other genes that are not modulated by the cAMP pathway (Sohn et al, 2003;Doedt et al, 2004;Harcus et al, 2004;Setiadi et al, 2006). Numerous in vitro and in vivo studies with efg1 mutants have demonstrated that Efg1 is important for C. albicans virulence and for the interactions of C. albicans with endothelial and epithelia cells, as well as biofilm formation and catheter infection (Lo et al, 1997;Phan et al, 2000;Dieterich et al, 2002;Lewis et al, 2002;Ramage et al, 2002;Garcia-Sanchez et al, 2004). Despite its importance, molecular mechanisms for how Efg1 regulates gene expression during hyphal development and other processes are still unknown.…”
Section: Introductionmentioning
confidence: 99%